ChemInform Abstract: Broensted Acid—Base Reactions with Anhydrous Sulfamates as a Pathway to [SO3N]3‐‐Containing Compounds: Preparation of Li3SO3N. Issue 5 (4th February 2014) - Kurzman, Joshua A.; Jouan, Gauthier; Courty, Matthieu; Palacin, M. Rosa; Armand, Michel; Recham, Nadir
Abstract Li3SO3N is prepared by ball‐milling LiSO3NH2 with a slight excess of LiNH2 or LiH for 4 h followed by annealing at 400—450 °C.